Buying Behaviour of Polish Urban Silver Singles: Choices of Market Products and Shopping Places - Tomasz Zalega (Gospodarka Narodowa. The Polish Journal of Economics, 2024)
The aim of the study is to identify and evaluate the buying behaviour of Polish silver singles concerning their choice of shopping places and the frequency of purchasing selected food and non-food products. The research was conducted in two stages from 2018 to 2022. The study shows that silver singles can be considered active consumers. Positive or negative attitudes towards shopping are determined by the age, education and wealth of the surveyed seniors. Shopping is a “big” or “very big” pleasure for young-old individuals (people aged 65–74), primarily women with a secondary or higher education, earning a monthly disposable income of over PLN 3,500. While shopping for food, silver singles prioritise price, quality and promotional offers, while fashion and the desire to stand out are of lesser concern. Conversely, when purchasing market products, they pay more attention to product quality than price. Single elderly people typically purchase food products at bazaars, marketplaces, corner shops and discount stores. For non-food products, they opt for big-box retailers as well as shops and showrooms located in shopping centres.